The green-restructuring of clusters: Investigating a biocluster's transition using a complex adaptive system model - Ram Kamath; Aitziber Elola; Frans Hermans (European Planning Studies, 2023)
Bioclusters' promise of helping achieving sustainable bioeconomies has invoked great interest among policymakers and academia. However, bioclusters are not intrinsically sustainable. If they are to fulfil their promise, bioclusters must undergo green-restructuring. While cluster-research has elaborated on green regional development, we need more clarity on how clusters transition to normatively desired states; we need more evidence of how green-restructuring unfolds. In this study, we conduct a longitudinal analysis to demonstrate how a biocluster green-restructures through the interactions of agency, regional and industrial structures, and phenomena at (supra-)national levels. To execute this analysis, we created a novel cluster-evolution framework that treats clusters, and the regional innovation system and sectoral systems of innovation that contain the cluster, as complex adaptive systems. We applied this framework to study the greening of the Basque pulp-and paper-biocluster, over four phases between 1986 and 2019. Our analysis helped us discover patterns of agency, structural dynamics, and of agency-structure interactions and how supra-regional phenomena shaped structures and agency over the four phases. Based on our findings, we recommend policymakers encourage not only green-tech entrepreneurs, but also institutional-entrepreneurs and place-leaders who can help shape both (supra-)regional and industrial structures.
Keywords: 320; green clusters; bioeconomy; path dependency; agency; place dependency; multiscalarity